Osmotic Resistance of Rat’s Erythrocytes After Local Cold Injury - Kovalov , Gennadiy; Chabanenko , Olena; Orlova, Natalia; Shpakova, Natalia (Problems of Cryobiology and Cryomedicine, 2022)
The effect of local cold injury in rats on the osmotic resistance of erythrocytes in the early and late reactive terms was investigated. Cryoinfluence was performed by pressing the applicator to the skin on the lateral surface of the rat thigh for 30, 60 and 120 s. Afterwards, the blood was collected from the aorta of animals after 1 and 4 hours and after 24 and 48 hours (early and late reactive periods, respectively). The effect of hypotonic solutions on cells was used as a test for osmotic resistance of erythrocytes. It is shown that the osmotic resistance of erythrocytes in the early reactive term increases (compared with control cells). In the late reactive term, the indices of osmotic resistance of erythrocytes after 24 hours approached the control values and after 48 hours they reached the norm. Osmotic resistance of erythrocytes in both reactive terms after local cold injury does not depend on the duration of cryoinfluence (30, 60, 120 s). The findings are considered from the standpoint of adaptive reactions that have an allostatic nature. Probl Cryobiol Cryomed 2022; 32(1): 024–033